EFFECT OF CURRENT RATIO, RETURN ON EQUITY, NET PROFIT MARGIN, TOTAL ASSETS TURNOVER, AND DEBT TO ASSETS RATIO ON FIRM VALUE - Diva Rifayani; Irni Yunita (SEAN Institute, 2023)
Firm value becomes an investor's view of the company's success and is often associated with the stock price. Therefore, companies are facing challenges to be able to maintain their performance. This study aims to analyze the effect of CR, ROE, NPM, TATO, and DAR on the company value of property & real estate sub-sector listed on the Indonesia Stock Exchange during 2016-2020. The sampling technique was purposive sampling. The population was 78 companies and the total sample for this research was 220 data from 44 companies. This research found that CR, NPM, TATO, and DAR have a positive significant effect on firm value. Meanwhile, ROE has negative significant effect on firm value. Simultaneously CR, ROE, NPM, TATO, and DAR have a significant effect on firm value.